Analysis of nursing professional practices under the perspective of the integrality of assistance to the woman - Xavier, Alana Gonçalves (2014)
This study aimed at reviewing the nursing professional practices under the perspective of the integrality of assistance to the woman. It is a descriptive and exploratory, qualitative study made in the county of Lagoa Seca, PB, Brazil, from October 2013 to February 2014. The techniques of participant observation, document analysis and semi-structured interviews were used. Practices of three nurses were evaluated, through interviews, analysis of medical records, observation in the waiting rooms and clinical assistance, using semi-structured script. From the technique of thematic content analysis, it was found that health promotion was contemplated only on an individual basis, the assistance is based on attendance restricted to complaints, and the care neglects various laws on health. It is considered that the professionals have the potential to develop integral assistance, however there is no commitment. The study indicates the need for changes in care practices in order to corroborate improvement concerning care.